Botulinum Neurotoxin-Producing Bacteria. Isn’t It Time that We Called a Species a Species? - Theresa Smith (American Society for Microbiology, 2018)
ABSTRACT Botulinum neurotoxins (BoNTs) are produced by a diverse set of seven clostridial species, though alternate naming systems have developed over the last 100 years. Starting in the 1950s, a single-species taxonomy where any bacterium producing BoNT would be designated Clostridium botulinum was introduced. As the extreme diversity of these strains was recognized, a secondary system of taxonomic “groups” evolved. It became clear that these groups also had members that did not produce BoNT, and in some cases, they were given formal species names. Genomic analysis now clearly identifies species affiliations whether an isolate is toxigenic or not. It is clear that C. botulinum group nomenclature is no longer appropriate and that there are recognized species names for each clostridium. We advocate for the use of the scientific binomials and that the single-species group nomenclature be abandoned.